Foraging patterns of four sympatric species of silversides (Atheriniformes: Atherinopsidae) in Lago de Pátzcuaro, Central Mexico - García-de-León, Francisco J (2014)
ABSTRACT: Since Barbour proposed sympatric speciation to explain evolution of silversides in the Lerma-Santiago basin, relatively little subsequent study has been done. We assessed foraging patterns of four sympatric silversides species (Chirostoma estor, Chirostoma grandocule, Chirostoma attenuatum and Chirostoma patzcuaro) in Lago de Pátzcuaro to understand resource partitioning and their sympatric coexistence. We assessed the abundance of invertebrate prey in three feeding habitats and measured physical and chemical habitat parameters at two study sites. Fish were collected during the wet (September 1987) and dry (March 1988) seasons; a total of 242 gut contents were analyzed. We evaluated the trophic guild of each species using the index of relative importance (IRI), prey selectivity with the Ivlev Electivity Index (E), dietary diversity using Shannon and Wiener diversity index (H’), and diet overlap using Morisita index. All silverside species were determined to be predacious carnivores that feed mainly on nekton and periphyton. Dietary diversity and prey selectivity patterns were similar among species and diet overlap was >70%. Our data do not support the proposition that coexistence of these four fish species is maintained by dietary specialization. We hypothesize that sympatric coexistence of atherinopsids in Lago de Pátzcuaro is explained by food resource availability and ontogenetic variation in their diets. This study highlights the importance of analyzing ecological patterns and mechanisms as basic elements for designing conservation strategies of species flocks, especially under habitat loss and introduction of exotic species. Conservation efforts are urgent to preserve the rare evolutionary process of sympatric speciation (habitat segregation) that is occurring in other lakes in central Mexico, and probably already lost in the Lago de Pátzcuaro, as a result of poor management and inadequate conservation strategies. KEY WORDS: Atherinopsidae, feeding interactions, species flocks, evolutionary process, conservation.